PENGARUH MANAJEMEN LABA TERHADAP BIAYA MODAL EKUITAS SETELAH KONVERGENSI SAK IFRS PADA PERUSAHAAN MANUFAKTUR - Ustman, Ustman (Fakultas Ekonomi, Program Studi Akuntansi, 2017)
The earnings information helps the owner or other party in estimating the profit power to estimate the risks in investment and credit. Profits are also used as a tool to measure the performance of the company's management over a period of time which is generally the concern of certain parties in assessing performance in management accountability in the management of resources entrusted to them, and can be used to predict future prospects. The existence of these reasons will encourage the emergence of earnings management practices.Companies that make earnings management will reveal less information in the financial statements to make their actions less easily detected, especially for information on the cost of equity capital. This study aims to determine the effect of earnings management on the cost of equity capital after the convergence of IFRS SAK. The measurement of earnings management used in this study is earnings management proxied by Discretionary Accruals, with modified jones model and cost of equity capital proxied by Ohlson model. The method of analysis used is multiple regression by mengguanakan secondary data. The research sample consisted of 30 manufacturing companies listed in BEI year 2013-2015 by using purposive sampling technique. The results prove that earnings management has no significant effect on the cost of equity capital after the convergence of IFRS SAK.